Present and Future Activities on Neutron Imaging in Argentina - Tartaglione, Aureliano (2015)
We present here a short review of the main work which has been done in the latest years in neutron imaging in Argentina, and the future plans for the development of this technique in the country, mainly focused in the design of a new neutron imaging instrument to be installed in the future research reactor RA10. We present here the results of the implementation of the technique in samples belonging to the Argentinean cultural heritage and experiments related with hydrogen storage. At the same time, the Argentinean RA10 project for the design and construction of a 30 MW multipurpose research reactor is rapidly progressing. It started to be designed by the National Atomic Energy Commission (CNEA) and the technology company INVAP SE, both from Argentina, in June 2010. The construction will start in the beginning of 2015 in the Ezeiza Atomic Center, at 36 km from Buenos Aires City, and is expected to be finished by 2020. One of the main aims of the project is to offer to the Argentinean scientific and technology system new capabilities based on neutron techniques. We present here the conceptual design of a neutron imaging facility which will use one of the cold neutron beams, and will be installed in the reactor hall. Preliminary simulation results show that at the farthest detection position, at about 17 m from the cold source, a uniform neutron beam on a detection screen with an intensity of about 108 n/cm2/s is expected.